EVALUATION OF SHEEP PRODUCTION PROJECT IN MOUSL TECHNICAL INSTITUTE - E. Ismael; Q Shamsal-dain; K. Rajib (Mesopotamia Journal of Agriculture)
Important sources for red meats in Iraq through the economical embargo was necessary to reach national security without import meat. The important objective to this study is the evaluation of animal production project especially sheep project which was the most from using the economical norm especially on going project evaluation. It was indicated that operating cost 77% , that mean that project was covered all total cost beside there were more financial return. The indicator of return of sales were 23% from the total return, while the benefit cost was 130% which mean the project gave 30% more economical return from total cost. The return on equity was one of the most benefit measures and indicated that the project was benefit and every 1000 I.D paid make benefit money 100 I .D. The pay back period for the project was almost 5 years, which means That the project can pay back all the money through this period. Finally break even point was indicated that benefits of project was more 902846 I.D than critical revenue , this mean the project was benefiting economically and its necessary to encourage to establishment more projects ,also according to production cirtal labor production was 13.83 I.D, which means that investment 1I.D. as labor in the project can achieved profit about 12.83, and capital productivity was 3.38 I.D., also the investment 1I.D can achieved profit 2.38 I.D. According to that net value cirtal was 7549006 I.D, which reach the net and gross values, that indicated decrease investment costs for these projects.